Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.268
|View full text |Cite
|
Sign up to set email alerts
|

The New Agora: Social Media as a Vector for Sign Language as a Language of Culture, Identity and Inclusion of the Deaf

Abstract: Sign Languages (SL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…According to a recent study (Guimarães & Fernandes, 2018) is significant for the needs of the deaf to find information in their daily lives. Information deemed necessary by people who are deaf includes original messages from their friends and conveyed by their community, delivered in a language they can understand together.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study (Guimarães & Fernandes, 2018) is significant for the needs of the deaf to find information in their daily lives. Information deemed necessary by people who are deaf includes original messages from their friends and conveyed by their community, delivered in a language they can understand together.…”
Section: Discussionmentioning
confidence: 99%
“…As Cuculick (2014, p. 123) notes, "such learning is key for social participation and productive citizenship." Supporting these findings, a study from Brazil found that social media were important for DHH youth who were geographically distanced from other DHH adolescents to better learn the sign language, engage in political movements and form friendships and intimate relationships with both DHH and hearing people (Guimarães & Fernandes, 2018).…”
Section: Icts Expanding and Intensifying Dhh Socialitiesmentioning
confidence: 91%
“…Similarly, Facebook has considerably influenced deaf college students in the US; through this platform, they could relate with multiple communities and learn more about their own families, social norms, current events and perspectives on various social issues (Cuculick, 2014). As Cuculick (2014, p. 123) notes, “such learning is key for social participation and productive citizenship.” Supporting these findings, a study from Brazil found that social media were important for DHH youth who were geographically distanced from other DHH adolescents to better learn the sign language, engage in political movements and form friendships and intimate relationships with both DHH and hearing people (Guimarães & Fernandes, 2018).…”
Section: Icts Expanding and Intensifying Dhh Socialitiesmentioning
confidence: 94%
See 2 more Smart Citations